2005
DOI: 10.1097/01.mat.0000179341.95404.f8
|View full text |Cite
|
Sign up to set email alerts
|

Energy Equivalent Pressure and Total Hemodynamic Energy Associated with the Pressure-Flow Waveforms of a Pediatric Pulsatile Ventricular Assist Device

Abstract: A pulsatile pediatric ventricular assist device (VAD) with a dynamic stroke volume of approximately 12 ml was tested to quantify the effect of flowrate and systolic duration on pulsatility as quantified by the energy equivalent pressure (EEP), defined as the hemodynamic energy per unit volume of fluid pumped. The VAD was tested on a mock circulatory loop, adjusted to maintain a systemic arterial pressure of approximately 90/60 mm Hg (systolic/diastolic) and a mean of 75 mm Hg. The EEP was calculated for each b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…Anticoagulation proved to be a challenge in this juvenile ovine model as has been reported by others (Carney et al 2009; Yamanaka et al 2006; Weiss et al 2005). Coumadin administration to achieve a PTR >1.5 was rare(see Figure 6A) with the Coumadin anticoagulation protocol used, and concurrent heparin administration continued for the 30-day study for each of the animals.…”
Section: Resultssupporting
confidence: 67%
“…Anticoagulation proved to be a challenge in this juvenile ovine model as has been reported by others (Carney et al 2009; Yamanaka et al 2006; Weiss et al 2005). Coumadin administration to achieve a PTR >1.5 was rare(see Figure 6A) with the Coumadin anticoagulation protocol used, and concurrent heparin administration continued for the 30-day study for each of the animals.…”
Section: Resultssupporting
confidence: 67%
“…The analysis results showed that the high pulse flow wave at 2Hz had the highest modulus at the first harmonics, followed by medium pulse at 2Hz, high pulse at 1Hz, medium pulse at 1Hz, low pulse at 2Hz and low pulse at 1Hz. In order to compare the energy dissipated by each flow waveform, EEP was calculated 32-34. This was given by the formula: EEP = (∫ pfdt ) /(∫ fdt ), where f is the pump flow rate, and p is the flow pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Ü ndar speculated that the extra energy of the pulsatile flow may help to provide better regional cerebral oxygen saturation. To further aid in the description of pulsatility, the concept of the extra or surplus hemodynamic energy (SHE), defined as the EEP minus the mean arterial pressure, was introduced by Ü ndar 24 and applied in the evaluation of heart-lung machines 25 and a pulsatile ventricular assist device 26 intended for pediatric use. The recent report of two patients successfully supported and weaned after pulsatile ECMO indicates a clinical interest in the advantages of pulsatile flow delivery beyond the short duration of a CPB run.…”
mentioning
confidence: 99%